A proteção da reserva florestal legal : um direito à equidade intergeracional - Gonçalves, Juliana Seawright (2015)
The environment has been dramatically transformed in recent years due to human action living to nominate risk society described by Beck with insecurities, uncertainties and risks on all sides. The Environmental Law brings important principles aimed at legal problems solution and aiming to achieve a means balanced and healthy environment for present and future generations. Within the panorama of the current environmental situation the protection of flora through the Office of Legal Forest Reserve (RFL) it is the object of this study. Thus, the RFL analysis was necessary since its inception in the Brazilian legal system, its goals and how it is today exposed in Law 12,651 / 12. There is a whole legislative process of recognition of this institute in Brazil and it has changed over time. The RFL protection should be prioritized in making state decisions, always in the progressive aspect, not admitting setbacks, so it failed to analyze Law 12,651 / 12 establishing the new forest legislation bringing major changes to legal and factual reality. However, the crux of the problem is the search for reasons for the RFL in the Brazilian legal system, joining issues such as the environmental function of the property, which is closely linked to the concept of sustainability, which aims to safeguarding the rights of future generations. A fundamental right and duty of respect to an ecologically balanced environment is observed as a right is related to a duty, an obligation and in this particular case, the owner has rights, but he/she also has duties, especially when it comes to property rural, which brings environmental peculiarities in soil conservation, water, climate, fauna and flora, aspects that favor the community, but also the very developed activity. To achieve the constitutional objective is necessary to achieving solidarity between state and society, aiming not only the present generation but also future, in recognition of intergenerational equity as Edith Brown Weiss theory. But the question goes even further, towards a true recognition of RFL as a tool, an imperative, based on a right to intergenerational equity.